Channel Islands Harbor Association of Lessees Invitation - Beth Anderson:::::: (1973)
A letter from Beth Anderson, the Executive Director of Channel Islands Harbor Association of Lessees, inviting the recipient to attend an annual dinner meeting to discuss the installation of officers, a summary of achievements, and see a guest speaker.